Computerbouw in Nederland: ondernemende academici en bedachtzame industriëlen - Alberts, Gerard (Studium, 2019)
In seemed that in the postwar years initiatives to construct computers were bound to be absorbed by the existing industry. And indeed Electrologica, the firm emerging from the mathematics research institute Mathematical Center, did find its end as Philips-Electrologica. But this was not because either Philips or Electrologica would have wanted this conclusion.In fact, there were not just this one, but a plethora of initiatives to build computers and several industrial enterprises did purchase an automatic calculating machine. But there was no easy fit. Most ideas brought to the fore with sparkling enthousiasm never made it to the stage of production, not even those which had resulted in a prototype computing machine. The exception was the ZEBRA computer, designed by Willem van der Poel of PTT research and finally taken into production by Stantec in Newport (Wales) –finally after frustrating refusal by PTT itself, by Philips and by Zuse KG. Philips also declined to join in a venture by Mathematical Center and Nillmy life insurance cy: Electrologica.Philips Industries did not evade the participation in a Dutch computer industry out ignorance. Both at the level of research and at the level of business policy and strategy, Philips new what was going on. No single entity in Dutch society was better informed that the board of Philips Industries. And it acted rationally according to all this knowledge. It played on a global level and would have its agreements with partners on the same level. In this case IBM was the partner and the agreement was that IBM purchase its components from Philips in exchange for Philips’s abstinence in the market of computer manufacturing. But even after that agreement had expired Philips was hardly interested in joining in a ‘national’ industry. If it did finally purchase the remnants of Electrologica, it did so to appropriate the expertise accumulated there.Finally, not only a view of Philips’own rationality in business strategies but also a view on the context of the Cold War with its characteristic relations between the hegemone US and the European states, helps to better understand the fate of Electrologica and the logic of it ending in Philips-Electrologica.